Modern methods of identification of adverse events associated with medication errors - A. P. Pereverzev; S. K. Zyryanov; Y. Sh. Guschina (Безопасность и риск фармакотерапии)
Prevention of adverse events caused by medication errors is an important challenge of modern healthcare as it offers the possibility to reduce mortality, improve patient safety and reduce costs arosed from correction of complications. Two modern methods (Global Trigger Tool and Failure Mode and Effect analysis) of detection and analysis of information about adverse events and medication errors are presented in the article, and according authors opinion can provide the opportunity to develop and suggest measures for reduction of potential risks.